Numerical Approximation of Granular Flow in a Container - Mohd Damanhuri, Nor Alisa; Ayob, Nor Syafikah; Harris, David (2017)
This poster presents a numerical approximation for the stress and velocity characteristics equations governing the plasticity flow of granular materials in a container satisfying the stress-equilibrium conditions, the Coulomb yield criterion and the double-slip kinematic equations.